Increasing the Competency of Water Farmer Farmers Regarding Sales Recording and Marketing Strategies in The Medium Village of Abiansemal Badung - PRILIANDANI, Ni Made Intan; KRISTIANTARI, I Dewa Ayu; SARI, Ni Made Taman (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
Most of the livelihoods of the residents of Medium Village are as water farmers. The  obstacle  faced  by  water  henna  farmers  in  Sedang  Village  is  the  lack  of knowledge  of  farmers  in  marketing  strategies  for  their  water henna  flower harvest,  apart  from  that,  water  henna  farmers  in  Medium  Village  still  have minimal knowledge  about  the  importance of making  a daily sales record book. The  solution  that  can  be  given  to  overcome  this  problem  is  by  providing knowledge  to  water  henna  farmers  in  the  Medium  Village  to  prepare  a  sales record book. This is done to help water henna farmers in the Medium Village to be able to know the profits they can make and be able to predict their financial performance. The next solution is to provide knowledge about online marketing media by utilizing social media, this is provided to help water henna farmers in Medium Village to be able to market their crops more widely.